Potential use of aquatic plants in constructed wetlands for simultaneous removal of Phosphate and COD from laundry wastewater - A Tefa, Marcorio; Harisuseno, Donny; Haribowo, Riyanto (Fakultas Teknik UB, 2018)
One component of household wastewater that has a bad impact on the environment is waste that comes from washing which uses detergent, due to a fairly high phosphate and chemical oxygen demand (COD) concentration. The purpose of this study was to determine the potential of using aquatic plants to reduce phosphate and COD levels from laundry waste. This research was carried out using constructed wetlands model of laboratory scale using the combination of flow types of subsurface flow systems (SFS) and the type of vertical flow system (VFS) with a waste residence time of 5 days and 10 days. Based on the results, for model I, the average percentage of COD levels reduction is 67.62% and phosphate is 13.89%, while in model II, the average percentage of COD reduction is 59.93% and phosphate is 14.36%, after 10 days of waste residence time. Aquatic plants used in the modeling of constructed wetland can grow and reproduce well, this can be indicated by the growth of newshoots and flowers of these plants.